Climatic zonation complicated the lithology controls on the mineralogy and geochemistry of fluvial sediments in the Heihe River basin, NE Tibetan Plateau. (30th January 2020) - Zhang, Jian; Geng, Haopeng; Pan, Baotian; Hu, Xiaofei; Chen, Liping; Wang, Wei; Chen, Dianbao; Zhao, Qiming
Abstract: Knowledge of the composition of modern fluvial sediments is important for understanding the combined effect of lithology and climatic factors on the erosion and sedimentation within drainage basins, However, this information is incomplete in arid and semiarid environments. In this study, 37 modern fluvial sediment samples were collected from the Heihe River and its major tributaries, in the NE Tibetan Plateau, and for analyses of heavy minerals, trace and rare earth elements (REEs) and grain size. The main aim was to explore the influence of erosion, transport and deposition processes on sediment composition, and to define appropriate provenance indicators specific to these rivers. Along the Heihe River, the amount of unstable minerals is abundant and not changing, these result suggests that chemical weathering plays only a minor role. The composition of six sediment samples obtained from the upper-middle reaches of Heihe River are influenced by hydrodynamic sorting processes, which resulted in enrichment of heavy minerals. In addition, the mineralogical and geochemical compositions lead to different conclusions regarding the contributions from tributaries to the sediments in the middle-lower reaches of the Heihe River. This may reflect the occurrence of contrasting hydrodynamic conditions in Heihe River and its tributaries which result in the transport of different size fractions. Moreover, the <63 μm fraction of the sediments from the Heihe River basin has been affected by inputs of eolian dust, which means that this fraction is less influenced by the rock types within the sediment source areas than is the case for the other size fractions. Therefore, we conclude that the sand fraction is more suitable for source to sink analysis of fluvial sediments within this and comparable environments. In the upper areas of the Fengle River basin, the combination of low temperature, sparse vegetation coverage and high precipitation have resulted in intense erosion. This case reminds us to note the effect of the climatic zonation on the provenance analysis in arid regions.